Unidad Educativa en Conocoto, Valle de los Chillos - Lastra Saltos, Diego Esteban (2017)
The University of the Americas in conjunction with the Municipality of Quito planned that a structuring proposal from the centrality Valley Chillos be held which is integrated with other centralities the Metropolitan District of Quito, for which the authorities of the UDLA assigned to Project Workshop ninth semester Architecture diagnosis and subsequent proposal of urban planning for this territory is carried out, the same as development in several stages, and presented to the municipality. The urban plan was developed based on all current and future needs, making a projection until 2025, where necessary equipments are created in the territory, which were organized and grouped into several platforms of equipment by region also noteworthy that the equipments relocations current risk zone are also performed. AII of these existing and proposed facilities form a structure of four subcentralities that are articulated to each other and have a specific character that was selected according to the existing vocation of the territory, thus forming the centrality of Chillos Valley. One of the subcentralities the master plan is the educational area that is created to potentiate the educational character of the sector and allow all people have access to education as it was one of the main problems identified in the diagnosis. In the educational area, specifically in Conocoto it is a platform of equipment where it is planned to carry out the design of the educational unit Conocoto most typology, which is created to meet the current needs of the population and that education is an indispensable right all citizens deserve and allows us to improve ourselves: Conocoto also is the parish that has the lowest rate of coverage of education throughout the Metropolitan District of Quito. The development of this project fits the guidelines of the urban development plan and is designed using many urban, architectural and sustainability criteria.